EFFECTS OF HIGH POWER LASER PLUS MANUAL THERAPY VERSUS MANUAL THERAPY ALONE ON MUSCLE ACTIVITY IN PATIENTS WITH CHRONIC CERVICAL RADICULOPATHY - Siamak Bashardoust Tajali; Hassan Namvar; Gholamreza Olyaie; Hossien Bagheri; Sharareh Saneie Sistani; Mohammad Hosienifar (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Muscles activity changes may occur in chronic neck pain, but there are few RCTs on speciﬁc changes in muscle activity chronic neck pain and also after using High Power Laser. The aim of this research was to study effects of High Power (H.P.) Laser plus Manual Therapy Versus Manual Therapy alone on Muscle Activity in Chronic Cervical Radiculopathy Patients.Materials and Methods: Frothy two patients with Chronic Cervical Radiculopathy were recruited for this double blind randomized clinical trial. The patients were randomly divided into Manual therapy plus H.P. Laser group and Manual therapy alone group. The Manual therapy plus H.P. Laser group was treated with High-Power Laser model K-LASER in addition to manual therapy. The Manual therapy alone group received suboccipital muscle release method, ULTT for median and radial nerve, chin tuck exercise, and resistance and stretching exercises. The interventions were conducted three times per week for 6 weeks. The activity of Flexor Carpi Radialis muscle (RMS) was evaluated before and after third and sixth weeks of the interventions by electromyography (EMG) instrument. The evaluations were also repeated two months after treatment accomplishment as follow up of the treatment effectiveness. The pain was assessed using Visual Analog Scale and the disability was assessed using Neck Disability Index questionnaire. Data were analyzed with multiple ANOVA Repeated measure and Bonferroni tests (p